La crise de l’esprit scientifique : une enquête, une tragédie, une redistribution collective des rôles - Eric Tannier; Vincent Daubin; Sophie Quinton (Les Cahiers de Framespa)
The process of scientific research resembles that of an investigator : observations, hypotheses, verifications, conclusions. In the case of ecological devastation, our community describes the state and dynamics of the contemporary world, tries to understand the causes in order to better propose means of action. But as is often the case for investigators, the possibility of their own responsibility is not often considered. For this, it is necessary to undertake a reflexive observation of one’s own functioning, and of the relationships that one weaves with the dynamics of the world. We report on the setting up of a possible instrument for this reflexivity, and how collective discussion makes it possible to find ways for scientists, at all organisational levels, to exercise their environmental responsibility.